Didactic strategy of literacy in mathematics for problem solving at the Colegio León XIII de Chiloé In Soacha (Memorias Sifored - Encuentros Educación UAN, 2021)
Implement a didactic strategy of reading and writing in mathematics in students from first to third of basic primary education of the Institución educativa León XIII Chiloé in order to favor learning processes to solve mathematical
Keywords: Solving mathematical problems; reading- math writing; descriptive qualitative approach